PATTERNS OF FINANCIAL CRIMES USING CRYPTOCURRENCIES - Boyko, A.; Dotscenko, T.; Dolia, Yu. (Socio-economic relations in the digital society, 2022)
The cryptocurrency market is rapidly gaining momentum and is becoming an alternative financial platform to the traditional financial trading market. Currently, cryptocurrency is of particular interest to criminals to make illegal profits, such as money laundering, terrorist financing, financing the proliferation of weapons of mass destruction, corruption. The main purpose of the study is to identify information signs that indicate the implementation of illegal financial transactions using cryptocurrencies. Empirical (observation, description) and theoretical (grouping, synthesis, abstraction) research methods were used for this research. According to the results of the study, it is established that the signs of illegal transactions with cryptocurrency are: non-transparent cryptocurrency contracts; encrypted cryptocurrency transactions; impersonal transactions; fragmented systematic transactions into marginal, limited amounts to avoid identification; transactions that do not comply with the approved transaction protocols; currency exchange transactions by unidentified traders; confusing cryptocurrency to other forms of electronic funds in order to withdraw such funds in cash. The authors of the article identify the main agents in the cryptocurrency economy (centralized and decentralized cryptocurrency exchanges, token issuers, distribution services, gaming services, cryptocurrency wallets). The paper describes software products for the identification of illegal cryptocurrency transactions. The results of the study are of practical value to national regulators in strengthening financial stability and combating illegal financial transactions. management of financial institutions to improve the system of counteraction to illegal financial transactions using payment cards, namely the creation of separate bodies for analysis and regulation of fraud in the banking sector, strengthening responsibility for fraud at the legislative level, establishing a single authentication standard for customers, development of open banking.
Keywords: fraud; payment instruments; bank cards; financial crimes